2019
DOI: 10.1371/journal.pone.0220726
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of vitrectomy for diabetic tractional retinal detachment in Chicago’s county health system

Abstract: Purpose To examine outcomes of 23-gauge (23G) pars plana vitrectomy (PPV) for complex diabetic tractional retinal detachment (TRD) in Chicago’s Cook County Health and Hospitals System (CCHHS). Materials and methods This is a retrospective noncomparative study of diabetic TRD cases that underwent PPV at CCHHS. Primary retinal reattachment rate, visual function, and postoperative complications were analyzed. Results Sixty nine consecutive cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 54 publications
1
37
1
2
Order By: Relevance
“…[ 10 12 ] In the era of microincision vitrectomy surgery, overall, the rates of final retinal reattachment have ranged from 67 to 100% with the rate of resurgery having fallen to 6–31%. [ 9 14 ] The rate of the final reattachment was 88.1% and 96.6% in our two groups, respectively. This could partly be explained by the higher proportion of complex detachments with macular involvement in the T1DM group.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…[ 10 12 ] In the era of microincision vitrectomy surgery, overall, the rates of final retinal reattachment have ranged from 67 to 100% with the rate of resurgery having fallen to 6–31%. [ 9 14 ] The rate of the final reattachment was 88.1% and 96.6% in our two groups, respectively. This could partly be explained by the higher proportion of complex detachments with macular involvement in the T1DM group.…”
Section: Discussionmentioning
confidence: 60%
“…[ 10 11 12 ] The outcomes of diabetic vitrectomy in older patients have been widely analyzed. [ 13 14 15 ] Only a few studies have analyzed the outcomes of surgery in young diabetic patients with PDR. [ 10 11 12 ] The previous studies have investigated possible predictors for DR in people with T1DM, however, there is an unmet need to evaluate the surgical outcomes following vitrectomy in T1DM patients.…”
mentioning
confidence: 99%
“…We found that 50% of our cohort experienced visual loss during the study period. This may seem to compare unfavorably with other published results of vitrectomy [11,19], but differences in study objective may serve to explain the discrepancy. Most studies evaluating the outcome of vitrectomy measure success based on visual acuity at a single point in time, and compare their results of patients with improved vision to those who experienced no improvement with surgery.…”
Section: Discussionmentioning
confidence: 54%
“…With recent advances in techniques of PPV, it is doing a great job in retaining, restoring of sight and prevention of blindness for patients of posterior segment diseases. Increasing number of posterior segment surgeries are being performed worldwide 6,7 . There were more male patients than females.…”
Section: Discussionmentioning
confidence: 99%